Forage fish and polycyclic aromatic compounds in the Fort McMurray oil sands area: Body burden comparisons with environmental distributions and consumption guidelines. (December 2019) - Evans, M.S.; McMaster, M.; Muir, D.C.G.; Parrott, J.; Tetreault, G.R.; Keating, J.
Abstract: The Fort McMurray region in northeastern Alberta (Canada) is rich in natural sources of polycyclic aromatic compounds (PACs) from exposed bitumen beds; anthropogenic sources are being released with increased oil sands industry expansion. Here we report on investigations of PACs (47 compounds) in three species of forage fish collected during the 2012–2013 Joint Oil Sands Monitoring Program (JOSMP) fish health investigations and compare results with PAC data for sediment and water collected under JOSMP and earlier programs. PAC concentrations in sediments varied three orders in magnitude and were highest at downstream tributary mouths, which flowed through the exposed McMurray Formation, and along reaches of the Athabasca River where the formation was exposed. PAC concentrations in water were less variable but with higher concentrations near exposed bitumen beds. Forage fish exhibited the weakest spatial gradients in ΣPACs concentration, which averaged 102 ± 32 ng/g in trout-perch from the Athabasca River, 125 ± 22 ng/g in lake chub from the Ells River, and 278 ± 267 ng/g in slimy sculpin from the Steepbank, Firebag, and Dunkirk Rivers. Low-molecular weight compounds, particularly naphthalenes and fluorenes, dominated fish PACs. Phenanthrenes occurred in greater percent composition in fish caught in areas where PAC concentrations in sediments were higher due to the proximity of bitumen sources than in other areas. Dibenzothiophene, a major component of bitumen PAC, was a minor component of fish ΣPACs. Forage fish PAC concentrations were below fish consumption guidelines established by the European Commission (2011) and for the reopening of the commercial fisheries closed by the Deepwater Horizon oil spill. PAC concentrations in forage fish were similar to concentrations observed in many other studies (fish market surveys, estuaries, and marine waters) and lower than in fish sampled from highly impacted areas (near refineries, harbors, and other industrialized areas). Graphical abstract: Image 1 Highlights: Spatial variability PAC concentrations in river sediments ranged over 3 orders of magnitude. Concentrations were highest where river erosion exposed bitumen from the McMurray formation. Spatial variability in PAC concentrations in forage fish was low. PACs in forage fish were dominated by low molecular-weight compounds. PACs concentrations in forage fish were below consumption guidelines. Abstract : PACs occur in low concentrations and spatial variability in forage fish in the Alberta oil sands area and below consumption guidelines.